Perlindungan Hukum Terhadap Kekerasan Perempuan dan Anak Di Kota Kupang - M. Dju Bire, Chatryen; Yopi Negong, Antonius (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2023)
Women and children are individuals who are most vulnerable to violent behavior in social life. Violence against women and children is not only physical violence but can also take the form of sexual, economic and psychological violence. Therefore, it is important for families to implement good and correct parenting patterns and always supervise children when playing, because perpetrators of crimes do not look at age and gender. Based on Law No. 35 of 2014 concerning Child Protection, the author has the impression that this policy is not working well. This can be seen from the discussion of problems that often occur, namely: Acts of violence against women and children are still very high in social life, especially in Kupang City.